PENGARUH OPERATING CAPACITY, PERTUMBUHAN PENJUALAN DAN FAKTOR-FAKTOR LAINNYA TERHADAP FIRM VALUE - THERESA YULIANTY; ARIES JONATHAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this research is to obtain empirical evidence regarding the effect of firm size, dividend policy, profitability, leverage, liquidity, operating capacity, and sales growth on firm value. The second objective is to identify the consistency of the test results of the independent variables on the dependent variable based on previous research findings. The data used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. Firm value is measured using Price to Book Value (PBV), while firm size, dividend policy, profitability, leverage, liquidity, operating capacity, and sales growth are measured using common financial ratios. The data were processed using SPSS version 25 and analyzed with multiple regression analysis. The results of this study indicate that profitability, leverage, and liquidity have a positive effect on firm value. Conversely, firm size, dividend policy, operating capacity, and sales growth have no significant effect on firm value. This means that companies with high profitability, leverage, and liquidity can increase their firm value in the eyes of investors or the market, either through higher profits or tax savings obtained from debt.